Social capital and local governance. A study of two Brazilian cities (Revista LIDER, 2020)
The main objective of this article is to examine the role of social capital and political institutions in citizens´ evaluation of public policy. In order to answer the questions proposed we analyzed two cities in Rio Grande do Sul, Brazil. In this context, we seek to go beyond a mere academic discussion dichotomized between institutionalists and culturalists, and we defend the idea that it is more productive to treat the issue of public policy, valuing both the cultural dimension (social capital) as well as the institutional dimension. The data utilized are from two research surveys with probabilistic samples that total 1.200 interviews, conducted between January and April of 2012. The results indicate that public policy evaluation by the population tends to be more positive, when both social capital and sound political institutions are present and are trusted by the citizens.